Die Grenzstadt als Touristenmagnet - Bongers, Marie (Eine besondere Nachbarschaft. Zusammenfassungen ausgewählter Abschlussarbeiten des Masterstudiengangs Niederlande-Deutschland-Studien = Een bijzonder nabuurschap. Samenvattingen van geselecteerde eindscripties van de masterstudie Nederland-Duitsland-Studies, 2023)
Keywords: Kleve (Kreis Kleve); Tourismus

Les pratiques du quotidien transfrontalières dans la Grande Région SaarLorLux - Wille, Christian (2019)
Abstract: „This paper analyses everyday practices carried out by the residents of the Saarland, Lorraine, Luxembourg, Rhineland-Palatinate and Wallonia in the neighbouring regions abroad. The key assumption is the consideration that the inhabitants of the Greater Region SaarLorLux define the transborder reality of life of this region through their cross-border performance of everyday practices. Such a socio-constructivist perspective is not interested in what the Greater Region SaarLorLux actually is, but in what ways it is constituted or how it manifests itself in the daily lives of its inhabitants. Therefor the most common cross-border everyday practices, such as shopping for everyday needs, leisure-time shopping, outdoor recreation/tourism, cultural events, as well as visiting friends and family are looked at in greater detail. These observations are based on selected findings from three recent empirical studies of the study region, which have been linked to each other as well as socio-culturally and socioeconomically mapped in order to carve out the spatial organization, the motives and other contextual factors of cross-border everyday practices in the Greater Region SaarLorLux. This approach allows reconstructing mobility flows and spatial emphases in the context of everyday practices and gives insights into the nature of cross-border living realities in the Greater Region SaarLorLux.“
Keywords: Alltag; Einkaufen; Familie; Internationale Mobilität; Saar-Lor-Lux; Tourismus

Grenzüberschreitende Alltagspraktiken in der Großregion SaarLorLux. Eine Bestandsaufnahme - Wille, Christian (Lebenswirklichkeiten und politische Konstruktionen in Grenzregionen. Das Beispiel der Großregion SaaLorLux. Wirtschaft – Politik – Alltag – Kultur, 2015)
Abstract: „In diesem Beitrag werden Alltagspraktiken untersucht, die von den Einwohnern des Saarlandes, Lothringens, Luxemburgs, von Rheinland-Pfalz und Wallonien in angrenzenden Regionen im Ausland ausgeführt werden. Dafür leitend ist die Überlegung, dass sich die Großregion SaarLorLux anhand der grenzüberschreitenden Ausführungen von Alltagspraktiken ihrer Bewohner als grenzüberschreitende Lebenswirklichkeit bestimmen lässt. In einer solchen sozialkonstruktivistischen Perspektive wird nicht danach gefragt, was die Großregion SaarLorLux ist, sondern auf welche Weisen sie konstituiert wird bzw. wie sie sich im Alltag ihrer Bewohner manifestiert. Dafür werden die am häufigsten grenzüberschreitend ausgeführten Alltagspraktiken näher betrachtet, zu denen das Einkaufen für den täglichen Bedarf, das freizeitorientierte Shoppen, das Erholen im Grünen/Tourismus, das Besuchen von kulturellen Veranstaltungen sowie das Besuchen von Freunden und Familienmitgliedern zählen. Die Betrachtungen basieren auf drei rezenten empirischen Studien im Untersuchungsraum und daraus ausgewählten Befunden, die zueinander in Beziehung gesetzt sowie soziokulturell und sozioökonomisch eingeordnet werden mit dem Ziel, die räumliche Organisation, die Motive und andere Kontextfaktoren von grenzüberschreitenden Alltagspraktiken in der Großregion SaarLorLux herauszuarbeiten. Über dieses Vorgehen werden Mobilitätsströme und räumliche Schwerpunkte im Kontext von Alltagspraktiken rekonstruiert und Einblicke gegeben in die Beschaffenheit von grenzüberschreitenden Lebenswirklichkeiten in der Großregion SaarLorLux.“
Keywords: Alltag; Einkaufen; Familie; Tourismus

Kulturgut, das der Krieg erschuf. Das bauliche Erbe der Befestigungs- und Verteidigungssysteme im SaarLorLux-Raum vom 16. Jh. bis zum 2. Weltkrieg - Reichert-Schick, Anja (Universität Trier, 2004)
Abstract: „The edificial structures of fortification and defense systems in the SaarLorLux region (Saar, Lorraine, Luxembourg) from the 16th century to World War II. Potential and problems of revaluation taking into consideration the recreation and tourism-oriented forms of use. Since the dispartment of the Carolingian empire in 843, territorial conflicts and dislocation of borders in the European SaarLorLux region have as a consequence led to the extraordinary high concentration of fortification and defense structures of different eras in this region. The fact that this has to be considered as unique was made clear by the Metz geographer François Reitel. He signified the SaarLorLux region as the world- "largest open air museum concerning fortification." Barely another region is able to document the evolution of modern times" fortification during the last five hundred years in such an impressive manner. The distinct variety of this period of fortifications is what makes it interesting for a diverse sightseeing tourism. Within the SaarLorLux region, leisure and tourism are important objectives for the conversion of fortifications as well as structures of defense. Both offer a vast potential of space not integrated in communal planning and are just partially built-up areas, extensive or even completely waste grounds with a reserve potential. Still, there is a gap between many abandoned and few fortifications in good, sometimes even outstanding condition. Therewith, fortifications in the SaarLorLux area are of great importance for culture tourism and their value is not recognized yet. The dissertation- objects of investigation are 333 buildings built in the three modern epochs stamped by the use of guns. In detail, those epochs are the one of bastion defense structures (16th to 18th century), the one of forts and huge defense structures (19th century) and the one of the territorial defense structures (20th century). A basic goal was the registration of the defense structural equipment in the SaarLorLux region documenting the different types, extents, functions and specialties of the existing objects. The registered buildings were judged for their adequacy for tourist and visitor use. In this way, it was possible to identify 25 fortifications and ensembles which have not been object of a conversion yet, but still have a potential for a future use in the tourism and recreation sector. Objects already in touristy use were analyzed and evaluated. Associations and clubs as supporters of this development find special account. After an evaluation of strengths and weaknesses of the existing tourism structures, perspectives for a future recreational and tourism use of the fortification heritage as a whole were developed.“
Keywords: Festung; Kulturerbe; Saar-Lor-Lux; Tourismus